Hypophysitis after COVID-19 vaccination in a patient with Rathke’s cleft cyst: A case report - Yuanyuan Yu; Guangxin Zhou; Junjie Du; Huijuan Zhu; Haojun Guan; Yongmin Bi; Da Zhang (Human Vaccines & Immunotherapeutics)
With the widespread vaccination of COVID-19 vaccine, a few cases have been reported that COVID-19 vaccine may cause endocrine disorders. A 59-y-old man presented with a loss of appetite after the first COVID-19 vaccination, which resolved spontaneously after 3 d. After the second COVID-19 vaccination, the symptoms including the loss of appetite, nausea, and vomiting reappeared and worsened along with loss of vision. He was found to have severe hyponatremia, and further investigations revealed secondary adrenal insufficiency, secondary hypothyroidism and Rathke’s cleft cyst. The patient responded well to glucocorticoid and levothyroxine supplementation, and at 1-y follow-up the patient developed hypogonadism. We hypothesize that hypophysitis is probably induced by COVID-19 vaccine and report the rare but serious adverse reactions for early recognition and intervention.